Ontology, action and truth. From Being and Nothingness to Truth and existence - Cladakis, Maximiliano Basilio (Estudios de Filosofía, 2015)
In this article we will discuss the manner in which the concept of truth that Sartre explains in his post- humous text Truth and Existence is supported by the fundamental premises of Being and Nothingness, while presenting topics that can be found in The Critique of Dialectical Reason and that put into question one of the fundamental premises of the 1943 text; the impossibility of an in-itself-for-itself.